2006
DOI: 10.1104/pp.106.083832
|View full text |Cite
|
Sign up to set email alerts
|

Species Preferentiality of the Pollen Tube Attractant Derived from the Synergid Cell ofTorenia fournieri 

Abstract: The synergid cell of Torenia fournieri attracts pollen tubes by a diffusible but yet unknown chemical attractant. Here we investigated the species difference of the attractant using five closely related species in two genera, namely T. fournieri, Torenia baillonii, Torenia concolor, Lindernia (Vandellia) crustacea, and Lindernia micrantha. These five species have an exserted embryo sac, and ablation experiments confirmed that their synergid cells attracted the pollen tube. When ovules of T. fournieri and one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 49 publications
1
69
0
Order By: Relevance
“…However, these interactions are also often the reason for the failure of a successful fertilization upon self-incompatible or interspecific and intergeneric crosses (Higashiyama et al, 2006;Escobar-Restrepo et al, 2007). Understanding the molecular basis of postpollination events in compatible crosses will undoubtedly provide new insights in how self-incompatibility and interspecific responses are regulated, as evidence emerges supporting an intrinsic link between the cellular pathways operating in both systems (Samuel et al, 2009 Several metabolic pathways were differentially regulated during the progamic phase.…”
Section: Swinging Partners: Regulation Of Signal Transduction and Celmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these interactions are also often the reason for the failure of a successful fertilization upon self-incompatible or interspecific and intergeneric crosses (Higashiyama et al, 2006;Escobar-Restrepo et al, 2007). Understanding the molecular basis of postpollination events in compatible crosses will undoubtedly provide new insights in how self-incompatibility and interspecific responses are regulated, as evidence emerges supporting an intrinsic link between the cellular pathways operating in both systems (Samuel et al, 2009 Several metabolic pathways were differentially regulated during the progamic phase.…”
Section: Swinging Partners: Regulation Of Signal Transduction and Celmentioning
confidence: 99%
“…Upon germination, the pollen tube grows from the stigma through the style and ovary tissues, where localized cellular interactions potentially define unique phases or checkpoints for pollen tube guidance. In flowering plants, compatible signaling molecules and chemical gradients produced by the female diploid tissues were identified as playing major roles supporting pollen tube growth and guidance along their way within the pistil Wu et al, 1995;Palanivelu et al, 2003;Dong et al, 2005), while more precise signals emitted by the female gametophyte should act as short-range attractants guiding pollen tubes into their final target, the embryo sac (Shimizu and Okada, 2000;Higashiyama et al, 2006). Specific signal interactions between pollen tubes and the embryo sac determine the final guidance steps toward sperm cell release into the embryo sac (Huck et al, 2003;Rotman et al, 2003;Higashiyama et al, 2006), a process that seems to be at least partially controlled by the female gametophyte (Escobar-Restrepo et al, 2007).…”
mentioning
confidence: 99%
“…In Arabidopsis thaliana, the myb98 mutant has a defective filiform apparatus and also fails to attract PTs, indicating that proper synergid differentiation is also necessary for PT attraction in other species [6]. Further PT attraction experiments in Torenia showed that a species-specific, diffusible signal is emitted from the synergids to attract the PT [7]. Small cysteine rich proteins (CRPs) have been implicated in many different phases of pollen-pistil interactions, from self-incompatibility early in pollination, to PT growth and guidance (reviewed in [8,9] been shown.…”
Section: The Synergid Cells: Gateway To the Female Gametophytementioning
confidence: 99%
“…The delay in the growth rate of the pollen tube in the cross with T. concolor may correspond to the phylogenic distance. Classification based on the photosynthetic gene rbcL suggests that T. fournieri and T. baillonii are a monophyletic group (Higashiyama et al 2006). Exceptionally, pollen tube growth in self-pollination of T. concolor tended to be less active than that observed in interspecific crosses with T. fournieri and T. baillonii, which did not correspond to phylogenic distance.…”
Section: Interspecific and Intergeneric Crosses Between Torenia And Smentioning
confidence: 85%